Perhitungan Kecepatan Terminal Obyek Jatuh di Udara - Edi Widodo, Catur (BERKALA FISIKA, 2006)
A program for determined terminal velocity of falling object in the air have been done with Python programming language version 4.2. Program was simulated interaction between massive object spheris with fluid gas (air). Program was construct by mean finite difference equation in object oriented programming Python. Object simulation is falling massive object spheris in static fluide. Input parameter is mass and radius object and viscosityÂ ofÂ fluid. Output is direction and velocity of object. The result of simulation indicated the terminal velosity is depend on mass and radius of objectÂ and viscosity of fluid.